Multipropriedade sustentável: a multipropriedade imobiliária no contexto das smart cities - Melo, Thanyson Dornelas de (2020)
This work aims to analyze the real estate multiproperty institute, created by Law nº 13.777/2018, within the context of smart cities. The phenomenon of urbanization, a reality in all countries of the world, encourages cities to seek new ways to develop, with sustainability and intelligence. In this context, real estate has an important role. The study contextualizes the right to property from its purely individual conception to the present day. Then, it addresses the main guidelines of Law nº 13.777/18, in parallel with the challenges that must be implemented by cities in this third millennium. The general objective is to verify, by means of an exploratory research, the guidelines applicable to smart cities, the main challenges imposed by disordered urban growth and the role that real estate multiproperty can play in the search for sustainable socioeconomic development. The deductive approach was chosen, based on bibliographic and documentary research techniques. It was observed that there is an individual and absolute concept guiding the current concept of sharing. As a consequence, property rights have been undergoing significant changes in their trajectory. At that moment, a greater awareness about the space where people live is ensured. Today, it must be emphasized that natural resources are finite and need to be used with maximum optimization. To this end, public policies and social conducts must be adopted in order to better use the possibilities of urban space. In this new conjuncture, compact and intelligent cities represent the best path for sustainable urbanization. However, it is necessary to revitalize the central areas of cities and to stop the increase in the urban sprawl. It is necessary to grow into cities, not outside. Another urgent) measure is to improve the offer of services, bringing people together. Finally, it should be noted that multi-ownership real estate has great potential to contribute to smart and rational urban development.